Managing Antimicrobial Resistance in Food Production: Conflicts of interest and politics in the development of public health policy - Williams-Jones, Bryn; Doizé, Béatrice (Les ateliers de l'éthique / The Ethics Forum, 2010)
Antimicrobial resistance is a growing public health concern and is associated with the over- or inappropriate use of antimicrobials in both humans and agriculture. While there has been recognition of this problem on the part of agricultural and public health authorities, there has nonetheless been significant difficulty in translating policy recommendations into practical guidelines. In this paper, we examine the process of public health policy development in Quebec agriculture, with a focus on the case of pork production and the role of food animal veterinarians in policy making.We argue that a tendency to employ strictly techno-scientific risk analyses of antimicrobial use ignores the fundamental social, economic and political realities of key stakeholders and so limits the applicability of policy recommendations developed by government advisory groups. In particular, we suggest that veterinarians’ personal and professional interests, and their ethical norms of practice, are key factors to both the problem of and the solution to the current over-reliance on antimicrobials in food production.